The Laboratory Investigation of the Effect of Calcium Chloride (CaCl₂) Derived from Duck Eggshells on the Thickening Time and Strength of Drilling Cement - Novrianti; Rico, Muhammad; Khalid, Idham; Purnamawati, Neneng; Herawati, Ira (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The thickening time and mechanical strength are vital in the performance of the drilling cement and are usually tested by API standards. The paper determines the role of duck eggshells' calcium chloride (CaCl2) as a natural accelerator on the cement slurry properties. CaCl2 was prepared by a regulating reaction between eggshell powder and 1M HCl and then was mixed with the Class G cement at the 1%, 2%, 3%, and 4% weight proportions. The experimental findings show that the most preferred performance is observed when the CaCl2 is 4 percent, which reduces thickening time to 128 minutes and increases compressive strength to 4,464.62 psi and shear bond strength to 370.28 psi. These results imply that using waste materials as the source of CaCl2 bio-based accelerators would be a viable source that would be environmentally viable in the optimization of drilling cements